Essays on Hume, Smith and the Scottish enlightenment - Berry, Christopher J. (Edinburgh studies in Scottish philosophy., 2018)
"This collection of essays by Christopher J. Berry spans several decades and multiple shifts across Scottish Enlightenment, Hume and Smith studies. It brings together classic essays – some of which are difficult to find – with 3 new pieces, which cumulatively constitute a distinct interpretation. Clustered around the themes of sociability, the Humean science of man and the Smithian engagement with commerce and morality, these collected works will be of considerable value to those working in political philosophy, the history of ideas and the history of economic and social theory. Also included is a substantial introduction which, alongside Berry’s personal intellectual history, provides a commentary on the development of the study of the Scottish Enlightenment." -- from the publisher